The Impact of Small Games use in Reducing Psychological Pollution and the Development of Psychological Skills and the Most Important Physical Abilities and Learn the Effectiveness of Running 100 Meter - Mohammed Abdulreda Salman (Journal of Global Pharma Technology, 2018)
The research problem is that there is a weakness in the technical performance of jogging efficiency 100 meters for students aged 11-12 years. The researchers found that the use of teachers for specific and non-varied methods in the education of students in addition to the lack of focus in developing the physical abilities of students, Pupils for this event. This has prompted researchers to study the problem to find appropriate solutions. Where the researchers saw the development of a program of motor education in the style of small games and include exercises to reduce the psychological pollution and develop psychological skills and the most physical capabilities as well as technical performance in the effectiveness of running 100 meters relay to ensure the level of performance of students to this event and the goal of the research to: Preparation exercises small games in reducing pollution and psychological development of psychological skills and the most important physical abilities of students aged (11-12 years). Find out the effect of small games in the style of artistic performance development ran 100 meters for students aged (11-12 years). The researchers used the experimental approach to design the equal groups to suit the nature of the study. The research community consisted of 6 primary pupils in Al-Farahidi Primary School for Boys in Babil Governorate (ages 11-12). The research society was the sixth primary pupils (28).Small games contributed to reducing the psychological pollution of the pupils by 11-12 years. The small games that have been used within the physical exercise capacity in the development of its effectiveness ran (100 m) and psychological skills for pupils Reconstruction (11-12 years).The approach taken by the teacher contributed to the reduction of pollution and psychological development of physical abilities and mental skills for pupils Reconstruction (11-12 years).Keywords: Small games, Psychological pollution and physical abilities.